The Effects of Textual Prompting and Reading Fluency on the Acquisition of Intraverbals - Emmick, Jill R (The Society for the Experimental Analysis of Behavior, Inc, 2010)
The study examined the effects of textual prompt fading on the acquisition of intraverbals in 3 individuals with developmental disabilities. An alternating treatments design was used to assess the two independent variables. The first independent variable was transfer of stimulus control without component skill fluency. The second independent variable was transfer of stimulus control with component skill fluency, in which participants were taught the textual responses used in the scripts to a level of fluency prior to transfer of stimulus control. The results suggest that transfer of stimulus control was effective for teaching intraverbals and that adding a fluency component resulted in faster acquisition for some participants.